PENETAPAN KADAR PROTEIN DAN ZAT BESI PADA TINTA CUMI-CUMI (LOLIGO Sp.) YANG BERASAL DARI KAB. PESISIR SELATAN SUMATERA BARAT - Tisa Mandala Sari; Martinus B.A; Oka Saputra (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2022)
Squid ink (Loligosp) is still considered a waste and has not been widely used as a food ingredient. This study aims to determine the protein content of squid ink tested using the Kjedahl method and the level of iron (Fe) using Atomic Absorption Spectrophotometry with air-acetylene flame at a wavelength of 248.3nm. The squid ink used is obtained from the South Coast. Qualitative testing of protein was carried out using the biuret, ninhydrin, and xanthoprotein tests which showed positive results. In the test, iron was reacted with NH4OH to form a reddish-brown precipitate which indicated that it was positive for Fe. From the measurements obtained protein content of 14.0733% and Fe content of 3.8 g/g. This protein and iron content can be used to meet daily protein and iron needs so that squid ink can be used as a food intake